Розвиток міжнародних транспортних перевезень в транскордонних регіонах - Прокудін, Георгій; Чупайленко, Олексій (Видавництво Львівської політехніки, 2015)
Formation of an international cross-border transport and logistics infrastructure meets international standards, increased productivity, transport and innovation activity of enterprises in the cluster, and provide for accelerated socio - economic development of the regions.
Development of international transport in transboundary regions